Adaptive co‐management for social–ecological complexity. Issue 2 (24th January 2008) - Armitage, Derek R; Plummer, Ryan; Berkes, Fikret; Arthur, Robert I; Charles, Anthony T; Davidson-Hunt, Iain J; Diduck, Alan P; Doubleday, Nancy C; Johnson, Derek S; Marschke, Melissa; McConney, Patrick; Pinkerton, Evelyn W; et al.
Abstract : Building trust through collaboration, institutional development, and social learning enhances efforts to foster ecosystem management and resolve multi‐scale society–environment dilemmas. One emerging approach aimed at addressing these dilemmas is adaptive co‐management. This method draws explicit attention to the learning (experiential and experimental) and collaboration (vertical and horizontal) functions necessary to improve our understanding of, and ability to respond to, complex social–ecological systems. Here, we identify and outline the core features of adaptive co‐management, which include innovative institutional arrangements and incentives across spatiotemporal scales and levels, learning through complexity and change, monitoring and assessment of interventions, the role of power, and opportunities to link science with policy.